Multifunctional Heat Pump Installation for Dairy Plants - Sit M.L.; Sit B.M. (Problems of the Regional Energetics, 2015)
The article presents the installation based on the approach using the integration of the carbon dioxide heat pump in pasteurization and cooling installation for milk and in installations for preparing of hot and "icy" water. The scheme differs from the prototype by the use of additional heat exchangers and of their connection to the main elements of the installation. A proposed technique of elements connection in the heat pump installation permits to compensate the effect of temperature of cold water supply source, which is low-grade heat source for the heat pump, on the quality the work of the installation. The design of the installation enables to compensate the impact of seasonal variation of water temperature. The installation ensures the COP = 5.3.